Management of Septic Arthritis of hip in preexisting inflammatory arthritis with total hip replacement - Bisht, Rishi; Maharjan, Rajram; Pariyar, Dipesh (Nepal Orthopaedic Association Journal, 2020)
Septic arthritis is often difficult to diagnose in presence of preexisting inflammatory arthritis. The classical signs of infection are absent and it is only high index of suspicion leading to diagnosis. Our case was a 45-year-old gentleman with inflammatory arthritis and avascular necrosis of femoral head. He had been planned for left total hip replacement after pathological fracture of femoral head. Intraoperatively, it turned out to be a case of septic hip. His infection was eradicated with thorough debridement and placement of antibiotic-laden spacer. He underwent two stage hip replacement and is doing well in the subsequent follow ups.